2003
DOI: 10.4049/jimmunol.171.1.166
|View full text |Cite
|
Sign up to set email alerts
|

CD28 and Inducible Costimulatory Protein Src Homology 2 Binding Domains Show Distinct Regulation of Phosphatidylinositol 3-Kinase, Bcl-xL, and IL-2 Expression in Primary Human CD4 T Lymphocytes

Abstract: Ligation of either CD28 or inducible costimulatory protein (ICOS) produces a second signal required for optimal T cell activation and proliferation. One prominent difference between ICOS- and CD28-costimulated T cells is the quantity of IL-2 produced. To understand why CD28 but not ICOS elicits major increases in IL-2 expression, we compared the abilities of these molecules to activate the signal transduction cascades implicated in the regulation of IL-2. Major differences were found in the regulation of phosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
147
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 147 publications
(154 citation statements)
references
References 64 publications
6
147
1
Order By: Relevance
“…Anti-CD28 ligation using Abs in vitro can stimulate signals that cannot be induced by the physiological ligands (32). Although the capacity of CD28 to rescue some signals appears to be PI3K independent, the PI3K signaling pathway may be required by other costimulatory receptors such as ICOS and OX40, and these can contribute to clonal expansion and differentiation in vivo (33,34). A failure of p110␦ D910A/D910A T cells to form functional conjugates with APCs or a state of anergy in a population of p110␦ D910A/D910A T cells may also help explain the reduced response to stimulation with APCs.…”
Section: Discussionmentioning
confidence: 99%
“…Anti-CD28 ligation using Abs in vitro can stimulate signals that cannot be induced by the physiological ligands (32). Although the capacity of CD28 to rescue some signals appears to be PI3K independent, the PI3K signaling pathway may be required by other costimulatory receptors such as ICOS and OX40, and these can contribute to clonal expansion and differentiation in vivo (33,34). A failure of p110␦ D910A/D910A T cells to form functional conjugates with APCs or a state of anergy in a population of p110␦ D910A/D910A T cells may also help explain the reduced response to stimulation with APCs.…”
Section: Discussionmentioning
confidence: 99%
“…The CD28 cytoplasmic domain that binds with a cytosolic protein called translationally controlled tumor protein (TCTP), a novel multifunctional antiapoptotic bcl-xL-interacting protein to regulate cell survival (72,73). In particular, one tyrosine (Y170 in mouse CD28, Y173 in human CD28) that is important in PI3K activation permits CD28 to recruit SH2-containing signaling molecules, including PI3K, Grb2, and Gads that control the regulation of bcl-xL (21,74). However, whether or not this regulation was dependent on mammalian target of rapamycin pathway is still controversial (13,75).…”
Section: Cell Survivalmentioning
confidence: 99%
“…In vitro studies have shown that CD28 signaling specifically upregulates the expression of the anti-apoptotic protein Bcl-x L , but not Bcl-2 [222]. Point mutation analysis has shown that tyrosine residue Y170 on the cytoplasmic tail of CD28 is essential for the recruitment of PI-3K, which induces the expression of Bcl-x L [223][224][225]. CD28 carrying a mutation at Y170 can promote T cell activation, proliferation and IL-2 production.…”
Section: Costimulatory Molecules and Anti-apoptotic Molecules In T Cellsmentioning
confidence: 99%